Clinal Variation at Phenology-Related Genes in Spruce: Parallel Evolution in FTL2 and Gigantea?. Issue 3 (1st July 2014) - Chen, Jun; Tsuda, Yoshiaki; Stocks, Michael; Källman, Thomas; Xu, Nannan; Kärkkäinen, Katri; Huotari, Tea; Semerikov, Vladimir L; Vendramin, Giovanni G; Lascoux, Martin
Abstract: Parallel clines in different species, or in different geographical regions of the same species, are an important source of information on the genetic basis of local adaptation. We recently detected latitudinal clines in SNPs frequencies and gene expression of candidate genes for growth cessation in Scandinavian populations of Norway spruce ( Picea abies ). Here we test whether the same clines are also present in Siberian spruce ( P. obovata ), a close relative of Norway spruce with a different Quaternary history. We sequenced nine candidate genes and 27 control loci and genotyped 14 SSR loci in six populations of P. obovata located along the Yenisei river from latitude 56°N to latitude 67°N. In contrast to Scandinavian Norway spruce that both departs from the standard neutral model (SNM) and shows a clear population structure, Siberian spruce populations along the Yenisei do not depart from the SNM and are genetically unstructured. Nonetheless, as in Norway spruce, growth cessation is significantly clinal. Polymorphisms in photoperiodic ( FTL2 ) and circadian clock ( Gigantea, GI, PRR3 ) genes also show significant clinal variation and/or evidence of local selection. In GI, one of the variants is the same as in Norway spruce. Finally, a strong cline in gene expression is observed for FTL2, but not for GI . These results, together with recent physiological studies, confirm the key role played by FTL2 and circadian clock genes in the control of growth cessation in spruce species and suggest the presence of parallel adaptation in these two species.